The Contribution of Science in Contemporary Fiqh Thought - Marwadi Marwadi; Mughni Labib; Muhajir Muhajir (CV. ULIL ALBAB CORP, 2024)
The development of science, especially from the West, to date is an inevitability that cannot be avoided. If you look at the history of the arrival of Greek science into the Islamic world, it brought Muslims to reach the peak of their glory in the Middle Ages. However, recently, the development of science in the Islamic world has stopped. After the Renaissance, philosophical and scientific thought in the West developed very rapidly. Along with the progress of science and technology in the West, religious values ​​have gradually shifted and even come into conflict with science. The implication of secularization in the West is that Muslims tend to abandon science and become a people left behind in the field of science. In fact, science is very necessary when Muslims need answers to contemporary fiqh problems. This research is library research with a qualitative approach. Data sources are documents related to the development of jurisprudence and sians. The data analysis technique uses content analysis. The research results show that from an Islamic perspective, there is no separation between fiqh and science. More than that, science and technology are tools used by humanity in carrying out the duties of its caliphate. Al-Qur'an and Sunnah of the Prophet PBUH. contains many verses and hadiths that provide information about natural phenomena, and encourage humanity to carry out ijtihad as a method of exploring Islamic jurisprudence or law. Therefore, there is no reason for today's Muslims to rise up and redevelop science and technology in carrying out their ijtihad in order to formulate contemporary jurisprudence that fulfills the objectives of enshrining Islamic law.